Empowering Type 2 Diabetes Patients through DIACOACH: A Mobile-Based Application for Virtual Health Coaching at Bajeng Primary Health Center - Jafar, Nuurhidayat; Setyawati, Andina; Bustamin, Anugrayani; Ahmad, Husnul Hatima; Sappewali, Andi Farhan; Fattah, Muh Shobur (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
Type 2 Diabetes Mellitus (T2DM) is a non-communicable disease with increasing prevalence, requiring effective management strategies. One of the main challenges in T2DM management is the low adherence of patients to a healthy diet, physical activity, and regular blood glucose monitoring. This community service program aims to improve glycemic control and the quality of life of T2DM patients through the implementation of Virtual Health Coaching (VHC) using the DIACOACH application at Bajeng Primary Health Center, Gowa Regency. The program involved 60 participants from the Prolanis group who received six weeks of health coaching using the Motivational Interviewing approach and the FIRA model (Focus, Identify, Reflect, Act). The DIACOACH application was used as an educational and self-monitoring tool for patients in managing their diabetes. This program included training on the application’s use, virtual coaching sessions by healthcare professionals, and an evaluation of the intervention’s effectiveness by assessing patients' health parameters before and after the intervention. The evaluation results showed an improvement in patients’ understanding of diabetes management and increased adherence to regular blood glucose monitoring. Additionally, the DIACOACH application received positive feedback regarding ease of use and benefits for participants. This community service initiative demonstrates that digital health technology in community-based healthcare services can be an innovative solution to support more effective and sustainable diabetes management.